ANALISIS CAMPUR KODE BAHASA INDONESIA DAN BAHASA JAWA DI MEDIA SOSIAL TWITTER - Balqis, Nur Amalia (Jurnal Komposisi, 2022)
Humans are social creatures who cannot be separated from the use of language to communicate. Communication occurs directly or on social media. The diversity of ethnicity, language, and culture can lead to the use of code-mixing in everyday life, especially when using social media. Code mixing can be found on Twitter social media. This study discusses the analysis of code mixing of Indonesian and Javanese on Twitter social media. The study used a qualitative descriptive method. The data source used by the author is screenshots of tweets on Twitter social media which contain a mix of Indonesian and Javanese codes. The results of the analysis in this study found the use of code-mixing on Twitter social media, namely code-mixing in Indonesian and Javanese. The dominant factors that cause the use of code-mixing are educational factors and social backgrounds, such as the environment where they live or the area where they live.